The GAGOme: a cell-based library of displayed glycosaminoglycans. (November 2018) - Chen, Yen-Hsi; Narimatsu, Yoshiki; Clausen, Thomas; Gomes, Catarina; Karlsson, Richard; Steentoft, Catharina; Spliid, Charlotte; Gustavsson, Tobias; Salanti, Ali; Persson, Andrea; Malmström, Anders; Willén, Daniel; et al.
Abstract Glycosaminoglycans (GAGs) are essential polysaccharides in normal physiology and disease. However, understanding of the contribution of specific GAG structures to specific biological functions is limited, largely because of the great structural heterogeneity among GAGs themselves, as well as technical limitations in the structural characterization and chemical synthesis of GAGs. Here we describe a cell-based method to produce and display distinct GAGs with a broad repertoire of modifications, a library we refer to as the GAGOme. By using precise gene editing, we engineered a large panel of Chinese hamster ovary cells with knockout or knock-in of the genes encoding most of the enzymes involved in GAG biosynthesis, to generate a library of isogenic cell lines that differentially display distinct GAG features. We show that this library can be used for cell-based binding assays, recombinant expression of proteoglycans with distinct GAG structures, and production of distinct GAG chains on metabolic primers that may be used for the assembly of GAG glycan microarrays. A CHO cell library displaying a near-complete repertoire of glycosaminoglycan (GAG) modifications provides a resource for cell-based binding assays, recombinant proteoglycan expression, and assembly of GAG glycan microarrays.